Strategy Formulation and Performance Of Saccos A Lyamujungu Sacco In Kabale District South Western Uganda - Agaba Moses; Turtasingura John Bosco (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The purpose of the study was to determine how strategic formulation affected Lyamujungu SACCO's organizational performance. A correctional sectional research design was used for the investigation. The study was able to analyze the link between the study variables since it used both quantitative and qualitative methodologies.Â Simple random selection and purposive sampling methods were used to choose a sample of 105 respondents. Using thematic analysis and SPSS Version 21.0, the respondents' quantitative and qualitative data were examined. Based on the study's objectives, quantitative findings in the form of descriptive statistics, correlations, and regressions were provided in tables. The study discovered that the development of a plan had a substantial positive association with SACCO organizational performance (r =.785, P .01). With these results, the study makes a contribution by channeling the currently fervent conversation surrounding concerns of strategic formulation and organizational performance in Lyamujungu SACCO by offering empirical evidence that has been mostly absent. The study advises management to collaborate with Board members and all other stakeholders to implement the resolutions of both the Board meeting and the Annual General Meeting in order for Lyamujungu SACCO to develop effective strategies. Â